Internet success a study of open-source software commons - Schweik, Charles M., 1961- (MIT Press, 2012)
Drawing on literature from many disciplines and using a theoretical framework developed for the study of environmental commons, Schweik and English examine stages of open-source software (OSS) development, presenting multivariate statistical models of success and abandonment.